WOMEN WHOM KOBZAR WAS IN LOVE WITH: THE STORY OF LOVE - Данилюк, Л. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article outlined Taras Shevchenko’s personal life – his love for women. These pages afford to supplement the poet’s biography, to have a new look at his creations.